1983
DOI: 10.1111/j.1600-0722.1983.tb00792.x
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of mercury from dental amalgam and mercuric chloride by oral streptococci in vitro

Abstract: – The capacity of the oral bacteria Streptococcus mitior, S. mutans and S. sanguis to methylate mercury was investigated in vitro. Mercuric chloride and pulverized dental amalgam in distilled water, respectively, were used as sources of mercury. Methylmercury was found in the bacterial cells of all three tested strains. The results indicate that organic mercury compounds may be formed in the oral cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 13 publications
0
25
0
2
Order By: Relevance
“…The families living with in the vicinity of the mines also use the heat of the smelting process for cooking. The methylation of Hg by intestinal or oral bacteria (27,28) may also be a source of MeHg for them. The average MeHg exposure level in the exposed group was estimated to be about 0.2 μg/kg/day, which is twofold higher than the reference dose level established by the United States Environmental Protection Agency (US EPA 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The families living with in the vicinity of the mines also use the heat of the smelting process for cooking. The methylation of Hg by intestinal or oral bacteria (27,28) may also be a source of MeHg for them. The average MeHg exposure level in the exposed group was estimated to be about 0.2 μg/kg/day, which is twofold higher than the reference dose level established by the United States Environmental Protection Agency (US EPA 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Organic mercury generated in the environment has been associated with bacterial activity [WHO, 1991]. It has also been shown that organic mercury compounds are formed by oral bacteria in vitro [Heintze et al, 1983]. In the light of these results, bacteria in the oral environment could be among the major sources of organic mercury in human saliva.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, secretion rates of unstimulated whole saliva were found to be negatively correlated with age both in males and females 8,9 as well as females alone. 10 Conversely, no significant influence of age on the stimulated salivary flow rate was observed in a crosssectional study of unmedicated adults conducted by Parvinen and Larmas. 11 Different results in adults were also obtained on the relationship between age and the concentration of either specific salivary proteins or total proteins in the whole saliva, 12 parotid saliva, [13][14][15][16] and submandibular/sublingual saliva.…”
Section: Introductionmentioning
confidence: 91%